More about Pascoli and his use of «novenario». La Voce’s analysis. - Conde Muñoz, Aurora (Cuadernos de Filología Italiana, 2004)
Poetical and metrical Italian studies still pay attention to Pascoli’s works not only as an essential contribution to XXth century poetry, but even and overall for their unexhaustible contents. This study is a new contribution which analyzes the Pascoli’s use of novenario in La Voce, one of the poems of his Canti di Castelvecchio, so much from the metrical perspective as the thematic in order to underline the complexity of Pascoli’s structures.